PENERAPAN AKUNTANSI IJARAH PADA PERBANKAN SYARIAH DI INDONESIA - Firmansyah, Amrie (Polytechnic of State Finance STAN, 2018)
This study aims to review the practice of ijarah accounting implementation in sharia banking in Indonesia. Ijarah is a lease transaction of an item and / or service between the owner of the lease object, including the ownership of use rights to the lease object with the lessee to obtain reward for the leased asset. This research uses the object of Ijarah iB Siaga Pendidikan product of Bank Bukopin Syariah.The research method used in this study using qualitative methods. The study was conducted during the period of February-June 2018. Interviews with the informants were conducted in the third week of May 2018. The selection of informants was based on employees of Bank Bukopin Syariah Branch Yogyakarta who mastered the accounting procedures of ijara. This research concludes that the implementation of ijarah / lease contract in iB Siaga Pendidikan financing by Bank Bukopin Syariah Branch of Yogyakarta has been in accordance with the principles of application of ijarah applicable in Indonesia. Furthermore, Bank Bukopin Syariah Branch Yogyakarta has outlined the ijarah accounting practice of Bank Bukopin Syariah Branch Yogyakarta in accordance with PSAK 107. However, the policy of Bank Bukopin Syariah in the initial lease of ijarah assets to be leased is not fully in accordance with the provisions in PSAK 107.